Maximum Power Point Tracking Using Fuzzy Logic Control (Port Said Engineering Research Journal, 2012)
This paper proposes an intelligent control method for the maximum power point tracking (MPPT) of a photovoltaic system under variable temperature and insolation conditions. This method uses a fuzzy logic controller applied to a DCDC converter device. The different steps of the design of this controller are presented together with its simulation. The PV system that I chose to simulate to apply my techniques on it is stand-alone PV water pumping system. Results of this simulation are compared to those obtained by the system without MPPT.  They show that the system with MPPT using fuzzy logic controller increase the efficiency of energy production from PV1